Impact of Environmental, Social, Governance (ESG) Disclosure on Company Performance - Tang, Sukiantono; Serly; Sheila Septiany; Budi Harsono; Windy Ardianti (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the impact of Environmental, Social, and Governance (ESG) disclosure on firm performance. Using secondary data from companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period, this study employs panel regression analysis with EViews software. The results indicate that ESG significantly influences firm performance with a negative relationship, suggesting that increased ESG disclosure has not yet provided a direct positive impact on financial performance. The implication of this study is that companies need to balance ESG commitments with sustainable business strategies to achieve long-term benefits.